Vibration and damping study of multifunctional grille composite sandwich plates with an IMAS design approach. (15th October 2021) - Li, Hui; Wang, Xintong; Hu, Xiaoyue; Xiong, Jian; Han, Qingkai; Wang, Xiangping; Guan, Zhongwei
Abstract: In the present study, an integrated material and structure (IMAS) design approach is proposed for fabrication of a multifunctional grille composite sandwich plate. It consists of two panels made of carbon fiber/resin polymer (CFRP) and one grille functional core that includes several grid frame beams (GFBs) and grille functional units (GFUs) via falcon riveting connections to achieve vibration sensing and damping control functions. In each GFU, it is composed of a rectangular grille (RG) and several embedded functional materials with 4-layer laminates, including a piezoelectric sensing layer, an upper copper wire layer, a magnetorheological elastomer (MRE) layer and a lower copper wire layer. To investigate the free vibration and damping characteristics of such a highly integrated sandwich structure, an analytical model is proposed that is based on the complex modulus method, the polynomial expansion approach, the improved Rayleigh-Ritz method, etc. After the natural frequencies, modal shapes and damping parameters are successfully solved, with results from literature being employed to roughly validate the model developed. Meanwhile, the dynamic experiments with different internal magnetic field distribution patterns and intensities of MRE are undertaken to give a further validation of the present model. Finally, the parameter analysis is carried out and some important conclusions are summarized to better exert active and passive vibration suppression performance of the CFRP-GFB-GFU plate. Graphical abstract: Image 1 Highlights: An integrated material and structure design approach is proposed for fabrication of a multifunctional grille composite sandwich plate. A dynamic model of the multifunctional plate studied is proposed to predict free vibration and damping characteristics. Numerical and experimental validations are conducted to prove the effectiveness of the present model. Parametric studies are performed to improve the structural vibration suppression capacity and stiffness performance.